Postoperative Reduction of Intraventricular Hemorrhage Volume: Single- Versus Dual-Catheter Drainage - Hussain, Syed Shahzad; Raza, Asif; Shahid, Saman; Asif, Hafiz Hamza; Ahmad, Usman; Ashraf, Naveed (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background/Aims The use of single/dual external ventricular drains (EVD) for reducing intraventricular hemorrhage (IVH) is under investigation. A randomized controlled trial was conducted to compare postoperative reduction of IVH volume using single- and dual-catheter drainage in spontaneous IVH patients. We investigated factors that may influence an effective hematoma volume reduction by EVDs.Materials and Methods The average cerebrospinal fluid (CSF) drainage volumes were analyzed. Computed tomography (CT) scans were performed on admission, 24 hours and 48 hours after EVD placement, and then on days 5 and 8. Patient group 1 was treated with a single EVD; patient group 2 was treated with bilateral EVDs. The IVH volume was calculated in all ventricles. A multivariate analysis was conducted to investigate variables that can influence the extent of hematoma volume reduction with a bilateral EVD. Regression followed by a Pearson correlation was performed to observe the strength of association of cofounders with the IVH volume reduction.Results The percentage of IVH volume change was found to be significantly higher in the dual-catheter group compared with the single-catheter group (p = 0.0034) after 5 days of EVD. The mean reduction in IVH volume was 17.36 (mL) in patients ≤ 45 years of age and 20.50 (mL) in patients > 45 years. The multivariate analysis suggested the following significant predictors for IVH volume reduction: age of the patient (p = 0.011) and longer duration (days) of EVD (p = 0.028). The age of the patient had a weak positive association and duration of EVD had a positive association with the IVH volume reduction.Conclusion Intraventricular drainage via bilateral EVDs may provide a better draining of blood-mixed CSF because it led to faster clot clearance. It is suggested that a longer duration of bilateral EVDs may lead to a greater reduction in IVH volume. Older patients may experience a greater IVH volume reduction by EVD because the volume of CSF increases with cerebral atrophy.
Keywords: external ventricular drainage; intraventricular hemorrhage; cerebrospinal fluid